2021
DOI: 10.1038/s41591-021-01413-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for increased breakthrough rates of SARS-CoV-2 variants of concern in BNT162b2-mRNA-vaccinated individuals

Abstract: The BNT162b2 mRNA vaccine is highly effective against SARS-CoV-2. However, apprehension exists that variants of concern (VOCs) may evade vaccine protection, due to evidence of reduced neutralization of the VOCs B.1.1.7 and B.1.351 by vaccine sera in laboratory assays. We performed a matched cohort study to examine the distribution of VOCs in infections of BNT162b2 mRNA vaccinees from Clalit Health Services (Israel) using viral genomic sequencing, and hypothesized that if vaccine effectiveness against a VOC is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
187
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(196 citation statements)
references
References 42 publications
6
187
2
1
Order By: Relevance
“…Our finding that B.1.1.7 and B.1.526 are not preferentially represented in the vaccine breakthrough group but distributed at similar proportions as other variants in case and control groups suggests that the studied mRNA vaccines are comparably effective against these predominant variants in the NYC area. This is in agreement with recent data from Israel evaluating B.1.1.7 in this context 17 . A sieve effect of the B.1.526 variant has not been studied in this detail, except for two studies with small sample sizes of n=2 and n=11 that did not allow strong conclusions 14,19 .…”
Section: Discussionsupporting
confidence: 94%
“…Our finding that B.1.1.7 and B.1.526 are not preferentially represented in the vaccine breakthrough group but distributed at similar proportions as other variants in case and control groups suggests that the studied mRNA vaccines are comparably effective against these predominant variants in the NYC area. This is in agreement with recent data from Israel evaluating B.1.1.7 in this context 17 . A sieve effect of the B.1.526 variant has not been studied in this detail, except for two studies with small sample sizes of n=2 and n=11 that did not allow strong conclusions 14,19 .…”
Section: Discussionsupporting
confidence: 94%
“…The copyright holder for this preprint this version posted July 15, 2021. ; https://doi.org/10.1101/2021.07. 13.21260273 doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.…”
mentioning
confidence: 99%
“…We next found that the virus detected among breakthrough cases matched the viruses circulating both temporally and spatially. Several reports have suggested increased breakthrough rates of SARS-CoV-2 variants of concern and variants with mutations known to escape antibodies in vitro [9][10] . In our investigation, when there was major transmission of the R.1 lineage, which contains the E484K mutation (known to escape antibodies in vitro 11 ), we saw several breakthrough cases with this lineage.…”
Section: Discussionmentioning
confidence: 99%